O portfólio reflexivo como estratégia mediadora da aprendizagem sobre ser docente de enfermagem - Cesário, Juleandrea Bido (2014)
The study has as object the learning about being a nursing professor mediated by the use of a reflective portfolio, from the perspective of students taking their master‟s degree at the Faculty of Nursing at the Federal University of Mato Grosso. The objectives were to: Understand the historical background of MES of discipline and the use of reflective portfolios in this context; Describe the Pedagogical Experiments adopted in the discipline; and Analyze the learning masters in nursing about being a teacher, mediated by the use of reflective portfolios as a pedagogical strategy, in that discipline. As theoretical grounding of the study, we brought the Liberating Pedagogy of Paulo Freire, who defends the liberating education instead of banking education. This is a qualitative study, in a descriptive and exploratory approach, participating 38 master students and 01 professor of the lecturer, with data collection done through documentary research - reflective portfolios and written statements of the years 2012 and 2013, discipline plans for the years 2006 to 2013, as well as semistructured interview with the said professor. Data were analyzed from the Operative Proposal. Thus, we find that the use of a reflective portfolio provided multiple learning about being a professor in nursing, namely the roles that teachers and students take when teaching strategies are used; (re)signification of the concept of professor, calling it nowadays educator, facilitator, mediator, stimulating, among others; as well the intrinsic characteristics of being a nursing professor. Considering this, the professor is the one that craves the formation of critical, reflective, and active subjects in the search for their own knowledge, educating themselves and the other of the unfinished condition before the knowledge. In addition, the professor was seen as responsible for the promotion of breaks with the traditional model, considering, for this, institutional norms, the context in which they are inserted, and the preparation and qualification of professors to explore teaching strategies. In this new learning environment, the student becomes the central actor in the educational process, developing interaction, communication and experience exchanging with the professor, through the feedback proposed by the reflective portfolio, that encourages the overcoming of difficulties, (re)construction of knowledge, and empowerment of the facilities and skills. Thus, it is possible to individually trace the path in search of learning, with autonomy, freedom and unique monitoring by the professor, making the student a realities changing agent. So, this teaching strategy was presented prosperous and efficient when it is intended to carry liberating educational practices.